Dui Paatan ke Beech Mein . Between the Devil and the Deep River - Sinha, Arvind (India, 1999)
Soros Documentary Fund Man-made floods devastated Bihar, India. Two million people were trapped and measures to deal with the impending massive floods were scarce. “Between the Devil and the Deep River” talks about development models which devastate the lives of millions, yet the powers remain unimpressed.